The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.3892/ijo.2017.3910
|View full text |Cite|
|
Sign up to set email alerts
|

All-trans retinoic acid restored the osteogenic ability of BMP9 in osteosarcoma through the p38 MAPK pathway

Abstract: Abstract. Osteosarcoma (OS) is the most common malignant bone tumour and is considered to be a disease caused by a dysfunction in differentiation. Bone morphogenetic protein 9 (BMP9) is the most potent osteogenic factor in mesenchymal stem cells, but it cannot induce osteogenic differentiation in OS cells; this might be one of the determinants in the pathogenesis of OS. All-trans retinoic acid (ATRA) can induce osteogenic differentiation of OS cells and potentiate BMP9-induced osteogenesis in preadipocytes. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…[11][12][13][14] Furthermore, it has been reported that ATRA also promoted osteogenic differentiation of different subtypes of OS cells both in vitro and in vivo. [15,16] Since ATRA (a vitamin A derivative) initially existed in the human body, it possesses negligible cytotoxic. [17] These results suggested ATRA was a potential and promising weapon against OS.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Furthermore, it has been reported that ATRA also promoted osteogenic differentiation of different subtypes of OS cells both in vitro and in vivo. [15,16] Since ATRA (a vitamin A derivative) initially existed in the human body, it possesses negligible cytotoxic. [17] These results suggested ATRA was a potential and promising weapon against OS.…”
Section: Introductionmentioning
confidence: 99%